1995
DOI: 10.1073/pnas.92.8.3416
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol inhibits luteinizing hormone-releasing hormone (LHRH) secretion by blocking the response of LHRH neuronal terminals to nitric oxide.

Abstract: It has previously been shown that alcohol can suppress reproduction in humans, monkeys, and small rodents by inhibiting release of luteinizing hormone (LH). The principal action is via suppression of the release of LH-releasing hormone (LHRH) both in vivo and in vitro. The present experiments were designed to determine the mechanism by which alcohol inhibits LHRH release. Previous research has indicated that the release of LHRH is controlled by nitric oxide (NO). The Alcohol suppresses reproductive function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 19 publications
4
78
0
Order By: Relevance
“…Since, NPY inhibited LH release in intact and castrated male and ovariectomized female rats (29,30), we hypothesize that NPY decreases the release of LHRH by inhibiting the noradrenergic neurons that have been shown to mediate pulsatile release of LHRH (31,32). Therefore, when the release of NPY is inhibited by leptin, noradrenergic impulses are generated that act on ␣ 1 receptors on the NO-ergic neurons, causing the release of NO, which diffuses to the LHRH terminals and activates LHRH release by activating guanylate cyclase and cyclooxygenase 1 , as shown in our prior experiments (31,32). The LHRH enters the portal vessels and is carried to the anterior pituitary gland, where it acts to stimulate FSH and particularly LH release by combining with its receptors on the gonadotropes.…”
Section: Discussionmentioning
confidence: 99%
“…Since, NPY inhibited LH release in intact and castrated male and ovariectomized female rats (29,30), we hypothesize that NPY decreases the release of LHRH by inhibiting the noradrenergic neurons that have been shown to mediate pulsatile release of LHRH (31,32). Therefore, when the release of NPY is inhibited by leptin, noradrenergic impulses are generated that act on ␣ 1 receptors on the NO-ergic neurons, causing the release of NO, which diffuses to the LHRH terminals and activates LHRH release by activating guanylate cyclase and cyclooxygenase 1 , as shown in our prior experiments (31,32). The LHRH enters the portal vessels and is carried to the anterior pituitary gland, where it acts to stimulate FSH and particularly LH release by combining with its receptors on the gonadotropes.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms proposed to explain the role of NO on the hypothalamic-pituitary-testicular axis involve effects at different levels (6). At the hypothalamic level, most studies have reported stimulatory effects (7)(8)(9), although inhibitory effects have been also reported (10). At the pituitary level, NO inhibits LH secretion (11).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, aminoguanidine is a 2 fold more potent inhibitor of iNOS from LPS-treated RAW 264.7 macrophages than L-NMMA (Misko etal., 1993), and L-NAME is a 3 fold less potent inhibitor of iNOS in the murine macrophage cell-line J774 compared to L-NMMA (McCall et at., 1991 (Ignarro 1984;Mayer et at., 1993) (Nakamori et at., 1994 (Mellion et al, 1981;Ignarro, 1991). This increase in cyclic GMP activates phospholipase A2 to provide arachidonic acid, the substrate for conversion by the activated COX to PGE2 (Canteros et al, 1995). Thus, the synergistic production of prostaglandins by NO and cyclic GMP may be involved in the pyrogenic effect of SNAP.…”
Section: Discussionmentioning
confidence: 99%